2019
DOI: 10.1111/jfbc.12766
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Cotoneaster integerrimus on in vitro and ex-vivo models of H2 O2 -induced lactate dehydrogenase activity in HCT116 cell and on lipopolysaccharide-induced inflammation in rat colon

Abstract: The present study evaluated the biological potential of methanol and aqueous extracts of the twigs and fruits of Cotoneaster integerrimus Medik. Lethality bioassays performed on Artemia salina showed that aqueous and methanol C. integerrimus extracts were non‐toxic in the concentration range (0.1–20 mg/ml), with a LC50 ≥ 2.5 mg/ml, for each single extract. The protective effect of the extracts was assessed in vitro against hydrogen peroxide‐induced lactate dehydrogenase (LDH) activity and tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The plant materials were dried in the shade at 24 • C (±0.5 • C) to achieve a constant weight [17]. Extracts were prepared using a mixture of methanol-acetone-water (3:1:1, v/v/v; 3 × 100 mL), and then sonicated at a controlled temperature (40 ± 2 • C) for 30 min [13]. The combined extracts were filtered, concentrated under reduced pressure, and after freezing, lyophilized in a vacuum concentrator (Free Zone 1 apparatus; Labconco, Kansas City, KS, USA) to obtain dried residues.…”
Section: Preparation Of the Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plant materials were dried in the shade at 24 • C (±0.5 • C) to achieve a constant weight [17]. Extracts were prepared using a mixture of methanol-acetone-water (3:1:1, v/v/v; 3 × 100 mL), and then sonicated at a controlled temperature (40 ± 2 • C) for 30 min [13]. The combined extracts were filtered, concentrated under reduced pressure, and after freezing, lyophilized in a vacuum concentrator (Free Zone 1 apparatus; Labconco, Kansas City, KS, USA) to obtain dried residues.…”
Section: Preparation Of the Extractsmentioning
confidence: 99%
“…The medicinal uses of Cotoneaster species in skin disorders have been reported in Pakistan, Turkey, India, Lebanon, and Iran as therapeutic agents in the treatment of cuts and wounds [13]. In addi-and Iran as therapeutic agents in the treatment of cuts and wounds [13]. In addition, an anti-itching effect of Cotoneaster has been observed [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in the literature, recently much focus has been devoted to screening novel drugs with anti-inflammatory potential isolated from various plant sources [ 51 ]. Anti-inflammatory activity has been reported for several Cotoneaster species [ 20 , 21 , 52 ]. In a recent comparative study of Cotoneaster leaves and fruits regarding their ability to inhibit lipoxygenase (LOX) and hyaluronidase (HYAL), all tested methanol-water (7:3) extracts were able to reduce the activity of both pro-inflammatory enzymes [ 20 , 21 ].…”
Section: Biological Activities Of the Genus Cotoneaster mentioning
confidence: 99%
“…Further studies on this species conducted in a model of colon cancer (the HCT116 cell line) showed that the tested fruits and twigs had the ability to decrease the activity of key inflammatory cytokines involved in the pathophysiology of ulcerative colitis. All aqueous and methanolic extracts, tested at 100 µg/mL, significantly reduced H 2 O 2 -induced TNFα gene expression, while the methanolic extract of twigs was the most effective at inhibiting lipopolysaccharide (LPS)-induced production of nitrite, prostaglandin E2 (PGE2), and 8-iso-prostaglandin F2α (8-iso-PGF2α) [ 52 ].…”
Section: Biological Activities Of the Genus Cotoneaster mentioning
confidence: 99%